Isolation and identification of bioactive compounds from twigs of Artocarpus Altilis - Omar, Muhammad Nor; Zuberdi, Ahmad Muzammil; Khan, Naik T.; Abdul Aziz, Muhammad Zahid; Kamal, Tara (Merit Research Journal, 2013)
The present study focuses on the bioassay guided isolation of antimicrobial compounds from Artocarpus altilis. The hexane, dichloromethane and methanol extracts were obtained from the dried (twigs of A. altilis) by using Soxhlet extraction. The plant crude extracts were evaluated for in vitro antimicrobial and antioxidant activities revealed that twigs part of A. altilis had potent antimicrobial activities, further purification had been done through column chromatography(CC) of dichloromethane and hexane extracts of A. altilis, which were afforded stigmasterol and cycloartenyl acetate respectively, the two compounds exhibited in vitro antimicrobial activity against S. aureus value of (11±0.5mm) and (11.3±0.5mm). Whereas minimum inhibition concetration (MIC) and minimum bactericidal/minimum fungicidal concetration (MBC/MFC) for isolated compounds were ranged from 62.5-500 µg/ml. Their structures were identified by 1H-NMR, 13C-NMR, IR and the spectra obtained were compared with previous data. This study forms a strong basis for declaring A. altilis as antimicrobial potential source to treat pathogenic microorganisms.